Hierarki Iblis dalam Pandangan Kristen Analisis Buku the Complete Book of Demonolatry Karya S. Connolly - Hutajulu, Muhammad Irgi Septiana; Harahap, Elly Warnisyah; Paralihan, Hotmatua (Lembaga Yasin AlSys, 2023)
The purpose of this study is to find out how the Christian view of the Devil's Hierarchy, and how the Devil's Hierarchy forms according to the book The Complete Book Oof Demonolatry, and how the Qur'an views the Devil's Hierarchy. This type of research uses library research through a normative theological approach. This thesis explores data from two sources, namely primary and secondary sources, the primary source is The Complete Book of Demonolatry by S. Connolly and secondary sources, namely articles, websites, books, literature, documents and the Bible. The research results show that Satan regulates the hierarchy evil spirits who inhabit the air and who help him to rule the kingdom of darkness. the term